The Pedagogical Leadership of the Spanish Teacher Before the New Language and Literature Programs: an Opportunity to Transform Realities - Chinchilla Araya, Tatiana (2022)
An ideal profile of the Spanish teacher is proposed in this document, by transferring, in a contextualized way, the pedagogical leadership skills that every teacher should develop for their work with the educational community, in specific relation to this subject and the objectives of pursued formations. The foregoing, as a way of reviewing the competencies and skills necessary for these professionals to be able to put into practice, in effective ways, the objectives and contents proposed in a new program that came to break the traditional schemes of the DLL in the Costa Rican institutions. The teacher must be convinced of the role that he has as a transformer of the reality of the classroom, as a potential and real leader of these changes in the learning of Language and Literature, for the good of society. The foregoing from the tools that the current study program allows, so that it is possible to glimpse changes in the communication skills of people, in the short term, which transcend the memorization of grammatical rules and uncritical readings. In this way, some critical visions were established on the way in which educators have perceived and applied the new parameters exposed in the current Spanish program, as well as a reflexive proposal on the profile of the Spanish teacher as a pedagogical leader, who has in hands the possibility that the ministerial proposal transcends the documents, in such a way that concrete changes are produced in the way of perceiving the subject of Spanish, by the educational community.